Peri-implant assessment via cone beam computed tomography and digital periapical radiography: an ex vivo study - Silveira-Neto, Nicolau (2017)
OBJECTIVES: This research evaluated detail registration in peri-implant bone using two different cone beam computer tomography systems and a digital periapical radiograph. METHODS: Three different image acquisition protocols were established for each cone beam computer tomography apparatus, and three clinical situations were simulated in an ex vivo fresh pig mandible: buccal bone defect, peri-implant bone defect, and bone contact. Data were subjected to two analyses: quantitative and qualitative. The quantitative analyses involved a comparison of real specimen measures using a digital caliper in three regions of the preserved buccal bone - A, B and E (control group) - to cone beam computer tomography images obtained with different protocols (kp1, kp2, kp3, ip1, ip2, and ip3). In the qualitative analyses, the ability to register peri-implant details via tomography and digital periapical radiography was verified, as indicated by twelve evaluators. Data were analyzed with ANOVA and Tukey's test (alpha=0.05). RESULTS: The quantitative assessment showed means statistically equal to those of the control group under the following conditions: buccal bone defect B and E with kp1 and ip1, peri-implant bone defect E with kp2 and kp3, and bone contact A with kp1, kp2, kp3, and ip2. Qualitatively, only bone contacts were significantly different among the assessments, and the p3 results differed from the p1 and p2 results. The other results were statistically equivalent. CONCLUSIONS: The registration of peri-implant details was influenced by the image acquisition protocol, although metal artifacts were produced in all situations. The evaluators preferred the Kodak 9000 3D cone beam computer tomography in most cases. The evaluators identified buccal bone defects better with cone beam computer tomography and identified peri-implant bone defects better with digital periapical radiography.